INOVASI PRODUK DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN BATIK JAMBI MARYANA - Ade Titi Nifita; Fenny Tialonawamarni (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
The purpose of this research are : (1) To identified and analyzed the impact of the product innovation simoutanously and partially towards the decision of Batik Jambi Maryana’s purchase. (2) To identified and analyzed the most dominant variable of the product innovasion that influenced the decision of purchasing Batik Jambi Maryana. This research is held in Jambi City and its sorroundings, by doing the survey methods. The sample came from 100 people that lives in Jambi and had purchased Batik Jambi Maryana more than once. The data was processed by using multiple regression analist tools. The research shows that all variable on the product innovation has an impact to the purchase decision both simoutanously and partially. Whilst the most dominant variable are complexity and communicability.